FPGA Implementation of a Probabilistic Neural Network for Spike Sorting - Xiaoping Zhu; Longtao Yuan; Dong Wang; Yaowu Chen (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Hardware implementation of Neural Networks (NNs) provides advantages such as parallelism and real-time capabilities, whereas Probabilistic Neural Networks (PNNs) achieve high accuracy in pattern discrimination. In this paper, a FPGA implementation of a PNN sorting algorithm is proposed to sort spikes. Both Matlab-based and FPGA-based sorting algorithms using a PNN were implemented and evaluated, and results show that FPGA's implementation is about 44.37 times faster than Matlab's realization with the same accuracy. This novel method indicates that the performance of current FPGAs is capable of portable device application.